Transforming Waste Into Wonders - Amy Zulaikha, Mohd Ali; Wan Jumani, Fauzi; Jamilah Bebe, Mohamad (UMPSA, 2024)
PEKAN, 1 August 2024 – In a significant effort to support the Ekosistem Kondusif Sektor Awam (EKSA) week at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), the Centre for Modern Languages (CML) held a one-day innovation exhibition focusing on upcycling waste materials into functional wonders.